Knowledge and Compliance of Oral Anticoagulation Therapy at Warfarin Clinic in Kathmandu: A Cross-sectional Study - Shakya, Roji; Maharjan, Muna; Karki, Sabita; K.C., Takma (Journal of Karnali Academy of Health Sciences, 2023)
Introduction: Warfarin is the most widely used anticoagulant drug worldwide due to its low cost and ease of use. Adequate knowledge and compliance to oral anticoagulation therapy are essential measures that decrease morbidity and mortality among cardiac patients. This study aimed to assess the level of knowledge and compliance regarding oral anticoagulation therapy among patients with a mechanical heart valve.Methods: A cross-sectional study was carried out among patients with mechanical heart valves on warfarin at Shahid Gangalal National Heart Centre of Kathmandu, Nepal. Participants were selected through a systematic random sampling technique, and a face-to-face interview was conducted. Knowledge was assessed using validated oral anticoagulation knowledge questionnaires composed of 20 multiple-choice questions. Compliance was assessed using 8 items Morisky Medication Adherence Scale. The descriptive and bivariate analysis were carried out using the Statistical Package for the Social Sciences version 16.Results: A total of 222 patients were included in this study. Only 35 (15.8%) had good knowledge, and 93 (41.9%) had high compliance to oral anticoagulation therapy. The mean adherence score was 1.81 ± 0.78. Age, literacy, and educational level of the patients were statistically significant with knowledge. The compliance was significantly related only with a duration of warfarin use (p=0.003).Conclusion: The patients had a moderate level of knowledge on warfarin therapy. However, they had good compliance with oral anticoagulation therapy. Based on the findings, education awareness program is recommended to improve the patient’s knowledge on oral anticoagulants